Historical-Theory of Traditional Forms of Music - Gaziev Jobirkhon Jurakhanovich (Researchparks Publishing, 2021)
A huge, invaluable spiritual and cultural heritage created by our ancestors for many centuries, the views of the Great Eastern scientists have been highlighted. Information on the status of shashmakom, Khorezm, our national music art is presented. Historical sources refer to the changes in the musical culture of Central Asia in the IX-XII centuries, written sources of Master musicologist scientists.